Draft Genome Sequence of Pseudarthrobacter phenanthrenivorans Strain MHSD1, a Bacterial Endophyte Isolated From the Medicinal Plant Pellaea calomelanos. (March 2020) - Tshishonga, Khuthadzo; Serepa-Dlamini, Mahloro Hope
Pseudarthrobacter phenanthrenivorans strain MHSD1 is a bacterial endophyte isolated from sterilized leaves of Pellaea calomelanos, a medicinal plant capable of growing in arid environments. Here, we report the draft genome sequence and annotation of this bacterial endophyte. The draft genome sequence of P. phenanthrenivorans strain MHSD1 has 4 450 468 bp with a G + C content of 65.30%. The National Center for Biotechnology Information Prokaryotic Genome Annotation Pipeline identified a total of 4004 protein-coding genes, 56 genes coding for RNAs, and 82 pseudogenes. Biosynthesis pathways for various phytohormones such as auxin, salicylic acid, ethylene, cytokinin, jasmonic acid, abscisic acid, and gibberellins were identified. Putative genes involved in various characteristics of bacterial endophyte lifestyle such as transport, motility, adhesion, membrane proteins, secretion and delivery systems, plant cell wall modification, and detoxification were identified. Phylogenomic analysis showed P. phenanthrenivorans strain MHSD1 to be a subspecies of P. phenanthrenivorans Sphe3.